Shiloh season - Naylor, Phyllis Reynolds (New York, NY Atheneum Books for Young Readers, 1996)
When mean and angry Judd, who has never known kindness, takes to drinking and mistreats his dogs, Marty discovers how deep a hurt can go and how long it takes to heal.
Sequel to: Shiloh.
78831
Keywords: Dogs -- Fiction; Kindness -- Fiction; West Virginia -- Fiction